Signifikasi Tanda dalam Larik Puisi “Risalah Min Taht Al-Maa” Karya Nizar Qabbani - Nazihah, Salma; Selviana, Ika (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
This research aims to examine the symbolic elements (signifier and signified) in Nizar Qabbani's poem "Risalah Min Taht Al-Maa" using Ferdinand de Saussure’s semiotic theory. The poem is rich in emotional depth and symbolic imagery, making it a fertile ground for semiotic analysis. Through a qualitative descriptive method, the researchers analyze how linguistic signs in the poem reflect deep emotional struggles, especially those related to love, pain, and psychological turmoil. The study finds that Qabbani's poetic expressions represent a symbolic system where every line contains signifiers that point to hidden and layered meanings (signifieds), highlighting the poet’s emotional state. The semiotic reading reveals that Qabbani's work is not just a personal narrative but a symbolic discourse on human emotional suffering.Keywords - Arabic Poetry, Emotional Symbolism, Ferdinand de Saussure, Nizar Qabbani, Semiotic Analysis.